2012
DOI: 10.1021/nn3011625
|View full text |Cite
|
Sign up to set email alerts
|

Supersensitive, Ultrafast, and Broad-Band Light-Harvesting Scheme Employing Carbon Nanotube/TiO2 Core–Shell Nanowire Geometry

Abstract: We demonstrate a novel, feasible strategy for practical application of one-dimensional photodetectors by integrating a carbon nanotube and TiO(2) in a core-shell fashion for breaking the compromise between the photogain and the response/recovery speed. Radial Schottky barriers between carbon nanotube cores and TiO(2) shells and surface states at TiO(2) shell surface regulate electron transport and also facilitate the separation of photogenerated electrons and holes, leading to ultrahigh photogain (G = 1.4 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 48 publications
1
54
0
Order By: Relevance
“…On the other hand, it has been recently shown that integrating a carbon nanotube and TiO 2 in a core/shell geometry with radial Schottky barriers regulates the electron transport and improves the separation of photo generated carriers increasing the photo gain while decreasing the recovery times. 5 Following this idea, in this work, we show that by covering a ZnO NW with MgO we were able to neutralise or passivate surface defects and to reduce the overall detrimental surface properties due to surface band bending. Our results demonstrate that a MgO shell, which provides confining barriers to electrons and holes within the ZnO core, enhances substantially the excitonic UV radiative recombination as well as the electrical conductivity.…”
mentioning
confidence: 74%
“…On the other hand, it has been recently shown that integrating a carbon nanotube and TiO 2 in a core/shell geometry with radial Schottky barriers regulates the electron transport and improves the separation of photo generated carriers increasing the photo gain while decreasing the recovery times. 5 Following this idea, in this work, we show that by covering a ZnO NW with MgO we were able to neutralise or passivate surface defects and to reduce the overall detrimental surface properties due to surface band bending. Our results demonstrate that a MgO shell, which provides confining barriers to electrons and holes within the ZnO core, enhances substantially the excitonic UV radiative recombination as well as the electrical conductivity.…”
mentioning
confidence: 74%
“…Some strategies have been proposed to improve the response speed. Zhou et al report the use of a one‐side Schottky‐contact geometry, which improves both sensitivity and response speed of a ZnO NW PD (response time ≈ 0.6 s) . Arranging the NWs in a network also shows an improvement of the recovery speed due to the formation of multiple junctions (recovery time ≈ 0.5 s) .…”
Section: A Comparison Of Response Speed For Different Types Of Zno Pdmentioning
confidence: 99%
“…To expand the waveleng th range of operation, photodetectors have been designed either by doping or by combining different functional materials. [3][4][5][6] Some of these complicated heterostructures involve complex fabrication processes, which restrict their widespread application. 3 For example, a multi-step fabrication scheme has been demonstrated for fabricating graphene/Ta 2 O 5 /graphene heterostructures for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Some of these complicated heterostructures involve complex fabrication processes, which restrict their widespread application. 3 For example, a multi-step fabrication scheme has been demonstrated for fabricating graphene/Ta 2 O 5 /graphene heterostructures for this purpose. 6 Therefore, the development of a single semiconductor material that can be easily synthesized and can achieve wide spectral sensitivity using a facile fabrication scheme would be extremely valuable.…”
Section: Introductionmentioning
confidence: 99%